1994
DOI: 10.1021/ac00094a026
|View full text |Cite
|
Sign up to set email alerts
|

Chiral Resolution of Cationic Drugs of Forensic Interest by Capillary Electrophoresis with Mixtures of Neutral and Anionic Cyclodextrins

Abstract: Chiral resolution of a number of cationic drugs of forensic interest (amphetamine, methamphetamine, cathinone, methcathinone, cathine, cocaine, propoxyphene, and various alpha-hydroxyphenethylamines) is achieved via capillary electrophoresis (CE) with added cyclodextrins (CDs), including novel mixtures of neutral and anionic CDs. In the latter studies, resolution and migration speed are readily adjusted by varying the ratio of the two added CDs, as the anionic CD acts as a counter-migrating complexing reagent.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
143
0
1

Year Published

1996
1996
2017
2017

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 260 publications
(145 citation statements)
references
References 40 publications
1
143
0
1
Order By: Relevance
“…While 4-methoxymethcathinone (R s = 1.17) and 4-fluoro-α-pyrrolidinoheptiophenone (R s = 1.10) enantiomers were partially separated, 3-methoxymethcathinone (R s = 2.31) and 4-methoxy-α-pyrrolidinopentiophenone (R s = 2.41) enantiomers were baseline separated. In addition to SBE-β-CD, heptakis(2,6-di-O-methyl)-β-CD (DM-β-CD) was applied to chiral separation of cathinone and methcathinone but different elution orders were shown [21]. While SBE-β-CD showed higher resolution for chiral separation of methcathinone (R s = 3.6) than DM-β-CD (R s = 1.0), mixing the two β-CDs worsened the separation (R s = 2.2).…”
Section: Capillary Electrophoresis (Ce)mentioning
confidence: 99%
See 1 more Smart Citation
“…While 4-methoxymethcathinone (R s = 1.17) and 4-fluoro-α-pyrrolidinoheptiophenone (R s = 1.10) enantiomers were partially separated, 3-methoxymethcathinone (R s = 2.31) and 4-methoxy-α-pyrrolidinopentiophenone (R s = 2.41) enantiomers were baseline separated. In addition to SBE-β-CD, heptakis(2,6-di-O-methyl)-β-CD (DM-β-CD) was applied to chiral separation of cathinone and methcathinone but different elution orders were shown [21]. While SBE-β-CD showed higher resolution for chiral separation of methcathinone (R s = 3.6) than DM-β-CD (R s = 1.0), mixing the two β-CDs worsened the separation (R s = 2.2).…”
Section: Capillary Electrophoresis (Ce)mentioning
confidence: 99%
“…UV DM-β-CD, SBE-β-CD a 1.9 -3.6 Chiral separation and identification of cathinone, methcathinone, phenalkylamines, cocaine and propoxyphene in forensic exhibits and khat plant materials [21] Cathinone, Methcathinone LIF NBD-F labelling + HS-γ-CD Chiral separation of cathinone, methcathinone and phenalkylamines [24] Methcathinone DAD β-CD Chiral separation and identification of methcathinone and phenalkylamines in clandestine tablets and urine a Separation and/or resolution factor(s) is/are obtained from using this/these chiral selector(s). b Total numbers of synthetic cathinones involved in the studies are shown instead of their identities, please refer to the original articles for their identities.…”
Section: Cathinone Methcathinonementioning
confidence: 99%
“…In this frame we were interested in the application of capillary electrophoresis, a technique, complementary to GC, endowed with similar characteristics of rapidity, selectivity and sensitivity, which is gaining importance in the forensic analysis [16] and which was applied to the separation of several amphetamine derivatives in the presence of chiral additives [17]. In this work, being not interested in chiral separations because the active principles contained in the vegetable material are enatiomerically pure, we tried to simplify the analytical method and to optimize the A capillary electrophoretic method, which allowed the detection and separation of the active principles of Catha edulis, i.e.…”
Section: Introductionmentioning
confidence: 99%
“…Many different types of instrumentation and methods have been utilized for the separation of cathinone analogs, including HPLC [102][103][104], GC [99,105,106], and CE [107][108][109][110]. Compared to HPLC and GC, CE demonstrates numerous advantages including high efficiency and resolution, and the capability to perform chiral separations through the addition of chiral selectors to the background electrolyte (BGE).…”
Section: Introductionmentioning
confidence: 99%
“…A major advantage of capillary electrophoresis over other separation techniques is its capability of separation in the area of chiral analysis [107][108][109][110]113]. Furthermore, the technique has wide applications in forensic toxicology, as demonstrated by the numerous papers published in the field by Fanali, Lurie, and others [109,[113][114][115][116].…”
Section: Introductionmentioning
confidence: 99%